2000
DOI: 10.1093/rheumatology/39.3.267
|View full text |Cite
|
Sign up to set email alerts
|

Familial vs sporadic rheumatoid arthritis (RA). A prospective study in an early RA inception cohort

Abstract: We show that sibship size is the only relevant risk factor for familial RA. No differences in genotypic and phenotypic characteristics, disease severity or radiological damage were observed among familial and sporadic RA. Familial history of RA is not a poor prognostic factor. This prospective study confirms previous cross-sectional findings in the Dutch population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
15
1
2

Year Published

2002
2002
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 29 publications
4
15
1
2
Order By: Relevance
“…For the prospective analysis of demographic and disease characteristics, data from 148 patients and 108 patients at 3 years and 6 years of followup, respectively, were available. For the whole patient group, the distribution of women (67%), IgM-RF positivity (82%), presence of HLA-DR4 (59%), and presence of the SE (65%) was comparable with that in previous studies (30,31). As shown in Table 2, no statistically significant differences in demographic or clinical features were observed, although the level of IgG-CCP antibodies tended to be increased in RA patients carrying the MIF Ϫ173C and/or the MIF CATT 7 allele (P ϭ 0.09 in both cases).…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…For the prospective analysis of demographic and disease characteristics, data from 148 patients and 108 patients at 3 years and 6 years of followup, respectively, were available. For the whole patient group, the distribution of women (67%), IgM-RF positivity (82%), presence of HLA-DR4 (59%), and presence of the SE (65%) was comparable with that in previous studies (30,31). As shown in Table 2, no statistically significant differences in demographic or clinical features were observed, although the level of IgG-CCP antibodies tended to be increased in RA patients carrying the MIF Ϫ173C and/or the MIF CATT 7 allele (P ϭ 0.09 in both cases).…”
Section: Resultssupporting
confidence: 85%
“…To this aim, a staged approach to model building was used, first by entering the known prognostic factors one by one, and then by adding the MIF Ϫ173GϾC and MIF CATT [5][6][7][8] functional variants. On the basis of observations in earlier studies, the following prognostic factors (independent variables) were included in the analysis: presence/absence of RF and IgG-CCP antibodies, HLA-DR4, the SE, and radiologic damage at baseline (30).…”
Section: Methodsmentioning
confidence: 99%
“…There is a wide range of results on the association between familial RA and radiographic progression. Some studies report a lack of association [17][18][19][20][21][22][23] and others a considerable influence of familial RA on damage progression [24][25][26][27][28][29]. These apparently contradictory results may be explained by differences in the definitions of familial RA and radiographic progression across studies, and in the study designs and statistical methods used ( Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…For the current study we examined the familial clustering of RA disease features utilizing a unique national resource of multicase families. Because some researchers have suggested that the clustering of RA cases within families is an artifact of large sibships (4–6), we also examined the distribution of siblings affected by RA and those without RA within this large sample of multicase families.…”
mentioning
confidence: 99%